2011
DOI: 10.1002/glia.21154
|View full text |Cite
|
Sign up to set email alerts
|

Loss of adenomatous polyposis coli in Bergmann glia disrupts their unique architecture and leads to cell nonautonomous neurodegeneration of cerebellar Purkinje neurons

Abstract: The tumor suppressor adenomatous Polyposis Coli (APC) is a multifunctional protein that inhibits the Wnt/beta-catenin signaling pathway and regulates the microtubule and actin cytoskeletons. Using conditional knockout (CKO) mice in which the APC gene is inactivated in glial fibrillary acidic protein (GFAP)-expressing cells, we show a selective and critical role for APC in maintaining the morphology and function of cerebellar Bergmann glia. APC-CKO mice developed Bergmann glia normally until the accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…Consistent with studies of non-neural stem cells (Lowry et al, 2005;Blanpain and Fuchs, 2009;Farin et al, 2012), our data show that Wnt/β-catenin signaling is only necessary for the terminal differentiation of specific neuronal progeny. Furthermore, and as shown for radial glia in other brain regions (Wang et al, 2011), we find that ectopic Wnt/β-catenin activity inhibits the expansion of neurogenic radial glia in the hypothalamus. Together, these data suggest that the most generally conserved role for Wnt pathway activity in neural progenitors is in promoting neurogenesis, and that other functions may differ between diverse stem and progenitor cell populations.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with studies of non-neural stem cells (Lowry et al, 2005;Blanpain and Fuchs, 2009;Farin et al, 2012), our data show that Wnt/β-catenin signaling is only necessary for the terminal differentiation of specific neuronal progeny. Furthermore, and as shown for radial glia in other brain regions (Wang et al, 2011), we find that ectopic Wnt/β-catenin activity inhibits the expansion of neurogenic radial glia in the hypothalamus. Together, these data suggest that the most generally conserved role for Wnt pathway activity in neural progenitors is in promoting neurogenesis, and that other functions may differ between diverse stem and progenitor cell populations.…”
Section: Introductionsupporting
confidence: 85%
“…Previous work from our laboratory showed that Wnt/β-catenin signaling is required for postembryonic hypothalamic neurogenesis , and other studies have also led to the hypothesis that pathway activity promotes radial glial differentiation (Lee et al, 2006;Wang et al, 2011Wang et al, , 2012Choe and Pleasure, 2012;Varela-Nallar and Inestrosa, 2013). By contrast, Wnt/β-catenin signaling has also been shown to promote the self-renewal and expansion of neural stem cells in the mammalian telencephalic subventricular zone and dentate gyrus (Qu et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…S5). Prior reports indicated that the interaction of APC with the cytoskeleton may regulate cell process formation and extension in radial glia, astrocytes and neurons (Imura et al, 2010;Wang et al, 2011;Yokota et al, 2009). In order to test the possibility that APC also controls process extension in Schwann cells, we traced and measured the length of these cells in 3DEM serial sciatic nerve sections of Apc lox/lox ;P0-Cre and Apc lox/lox control mice.…”
Section: Apc Loss In Schwann Cells Leads To Perturbed Extension Of Prmentioning
confidence: 99%
“…Prior reports indicated that APC in the CNS regulates process formation and extension by radial glia, astroglia, and neurons, proliferation of neuroblasts, and trophic interactions between Bergmann glia and Purkinje cells (Yokota et al, 2009; Imura et al, 2010; Wang et al, 2011). A recent study (Fancy et al, 2009) demonstrated that oligodendroglial differentiation and remyelination are delayed in adult Apc min/+ mice ( Apc multiple intestinal neoplasia, one-allele truncated mutation of Apc , lacking β-catenin binding domain ) (Moser et al, 1993) following lysolecithin-induced demyelination, and suggested, but did not prove, that this delay was attributable to dysregulation of Wnt/β-catenin signaling in these Apc -haploinsufficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…Does single-allele APC truncation lead to upregulation of Wnt/β-catenin signaling in the CNS? Since axonal activity regulates OPC differentiation (Barres and Raff, 1999), were the delays in oligodendrogenesis and remyelination secondary to axonal dysfunction elicited by the Apc mutation (Zhou et al, 2004; Chen et al, 2011; Wang et al, 2011), or does APC exert cell-autonomous effects on oligodendroglial differentiation?…”
Section: Introductionmentioning
confidence: 99%